2016
DOI: 10.1038/srep32364
|View full text |Cite
|
Sign up to set email alerts
|

Using spatial uncertainty to manipulate the size of the attention focus

Abstract: Preferentially processing behaviorally relevant information is vital for primate survival. In visuospatial attention studies, manipulating the spatial extent of attention focus is an important question. Although many studies have claimed to successfully adjust attention field size by either varying the uncertainty about the target location (spatial uncertainty) or adjusting the size of the cue orienting the attention focus, no systematic studies have assessed and compared the effectiveness of these methods. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The primary goal of the dot stimulus was to present a broadband, isotropic, and spatially-localized stimulus that would be free from the bias towards specific orientations, features, and regions. This stimulus has been largely used to investigate the processes of spatial attention [29][30][31][32]. It was also superior than grating acuity because oriented gratings suffer from meridional neural bias, which may cause orientation-dependent difference in acuity.…”
Section: Experimental Designmentioning
confidence: 99%
“…The primary goal of the dot stimulus was to present a broadband, isotropic, and spatially-localized stimulus that would be free from the bias towards specific orientations, features, and regions. This stimulus has been largely used to investigate the processes of spatial attention [29][30][31][32]. It was also superior than grating acuity because oriented gratings suffer from meridional neural bias, which may cause orientation-dependent difference in acuity.…”
Section: Experimental Designmentioning
confidence: 99%
“…Herrmann et al ( 2010 ) confirmed such manipulation; using fMRI, they showed a larger spatial extent of increased neural activity in V1 when observers performed the task with than without spatial uncertainty. Attention-field size is also affected by cue size (e.g., Yeshurun & Carrasco, 2008 ), but that manipulation may not be as effective as spatial uncertainty (Huang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Psychophysical studies have confirmed some of these predictions for covert spatial attention by manipulating the attention-field size via spatial uncertainty of stimulus locations (Herrmann et al, 2010 ) and for feature-based attention by manipulating the uncertainty range of the relevant features (Herrmann, Heeger, & Carrasco, 2012 ). Indeed, a recent study has confirmed that spatial uncertainty of the target location is an effective manipulation of attention-field size (Huang, Xue, Wang, & Chen, 2016 ).…”
Section: Introductionmentioning
confidence: 95%
“…In order to optimise the selection of relevant information from a rich visual world, the focus of attention can be flexibly changed in several ways: it can, for example, be shifted from one object or location to another (attentional orienting;LaBerge, 1995;Posner, 1980;Weichselgartner & Sperling, 1987) or it can be expanded or contracted in spatial extent to encompass larger or smaller objects (attentional focusing; Benso, Turatto, Mascetti, & Umiltà, 1998;Castiello & Umiltà, 1990;Eriksen & Yeh, 1985;Huang, Xue, Wang, & Chen, 2016;Jefferies, Gmeindl, & Yantis, 2014). It has been intensely debated whether the focus of attention can also be divided and deployed independently to spatially separated objects or locations.…”
Section: First Unitary Then Divided: the Temporal Dynamics Of Dividimentioning
confidence: 99%